1987
DOI: 10.1073/pnas.84.20.7075
|View full text |Cite
|
Sign up to set email alerts
|

Light-stimulated inositolphospholipid turnover in Samanea saman leaf pulvini

Abstract: Leaflets of Samanea saman open and close rhythmically, driven by an endogenous circadian clock. Light has a rapid, direct effect on the movements and also rephases the rhythm. We investigated whether light signals might be mediated by increased inositolphospholipid turnover, a mechanism for signal transduction that is widely utilized in animal systems. Samanea motor organs (pulvini) labeled with H3llinositol were irradiated briefly (5-30 sec) with white light, and membrane-localized phosphatidylinositol phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 26 publications
(31 reference statements)
1
51
0
Order By: Relevance
“…We have previously demonstrated that the levels of two lipids, tentatively identified as PIP and PIP2, decrease on illumination of S. saman pulvini, simultaneously with increasing levels of inositol phosphates (19). The present unequivocal confirmation of these tentative identifications strengthens our hypothesis of PI cycle involvement in light reception in pulvini.…”
Section: Lysopi In S Saman Pulvinisupporting
confidence: 79%
See 1 more Smart Citation
“…We have previously demonstrated that the levels of two lipids, tentatively identified as PIP and PIP2, decrease on illumination of S. saman pulvini, simultaneously with increasing levels of inositol phosphates (19). The present unequivocal confirmation of these tentative identifications strengthens our hypothesis of PI cycle involvement in light reception in pulvini.…”
Section: Lysopi In S Saman Pulvinisupporting
confidence: 79%
“…We have demonstrated the existence of inositol phosphate and inositol phospholipid components of the PI cycle in S. saman pulvini (5,18) and have shown light-stimulated metabolism of these components (19). In these studies the inositol phospholipids were separated by TLC.…”
mentioning
confidence: 99%
“…There are few reports in the literature concerning polyphosphoinositide turnover in plants in response to stimuli. Recently, light-induced polyphosphoinositide turnover in Samanea saman pulvini and auxin-induced polyphosphoinositide turnover in Catharanthus roseus cells have been reported (8,17). However, the connection between the time course of the polyphosphoinositide turnover and the elevation of free Ca2+ in the cytosol in response to light or auxin has not been delineated.…”
mentioning
confidence: 96%
“…A few studies of DAG levels in plants or plant organelles (20) have reported higher DAG concentrations. For example, Morse et al (21) found DAG of Samanea saman pulvinus to vary from 3.5 nmol/100 nmol PL in darkacclimated tissue to 4.2 nmol/100 nmol PL following exposure to light conditions that induce PIP2 hydrolysis.…”
mentioning
confidence: 99%